RAMAN SPECTROSCOPY OF GOLD CHLORO-HYDROXY SPECIATION IN FLUIDS AT AMBIENT TEMPERATURE AND PRESSURE: A RE-EVALUATION OF THE EFFECTS OF PH AND CHLORIDE CONCENTRATION - I. SOLUBILITY AND HYDROLYSIS REACTIONS OF GOLD IN AQUEOUS SOLUTION - Murphy P.J.; LaGrange M.S. (My University, 1998)
Previous work on gold chloride and hydroxide speciation in fluids has shown differences in opinion as to the relative importance of gold (I) and gold (III) species, as well as for the Raman peak assignments for the various species. In addition, previous experimental work has not been consistent with theoretical predictions either of the number or of the frequencies of the peaks in the Raman spectrum. In order to re-evaluate the effect of pH on Raman spectra and speciation, solutions containing gold (III) chloride were analysed by Raman spectroscopy at ambient temperature and pressure, over a range of pH from 1 to 11. Total gold concentrations were from 0.001 to 0.02 M, with total chloride concentrations of 0.004-0.5 M. The spectra obtained are consistent with the hydrolysis sequence of square-planar Au(III) complex ions [AuClx(OH)4-x]-, where x = 0-4. The Au-Cl stretching peaks obtained were 348/325 Rcm-1 for [AuCl4]-, 348/335/325 Rcm-1 for [AuCl3(OH)]-, 337/355 Rcm-1 for [AuCl2(OH)2]-, and 355 Rcm-1 for [AuCl(OH)3]-. [Au(OH)4]- probably occurred, alongside [AuCl(OH)3]- at pH values above 11. A dark purplish-grey precipitate (Au(I)OH) formed at high pH values. No evidence for Au(I) species was found. The spectra are more consistent with theory than previous data and show the predicted number of peaks for Au-Cl and Au-OH stretches for each species. However, the peak frequencies do not fit precisely with the predictions of Tossell (1996), particularly for Au-OH stretches. Hydrolysis of the simple chloride species occurs at lower pH values than found previously, and both gold and chloride concentration were found to affect the pH ranges of stability for the various chloro-hydroxy species. Decreasing gold concentration resulted in hydrolysis occurring at lower pH values. This is especially important in the absence of excess chloride (ΣCl = 4ΣAu). Substantial hydrolysis occurred below pH = 4 for 0.02 M Au /0.08 M Cl-, and below pH = 2 for 0.001 M Au / 0.004 M Cl-. Addition of excess chloride (as NaCl) increases the pH of hydrolysis at a given gold concentration.